El papel de la matemática en el proceso educativo inicial - Guzmán, M. de (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
A short analysis of the educational values of Mathematics and of the main defects that can be observed in the current trends in Spanish primary and secondary schools, together with some remedial suggestions.